A Pilot Study Evaluating the Effectiveness of Platelet-Rich Plasma Therapy for Treating Degenerative Tendinopathies: A Randomized Control Trial with Synchronous Observational Cohort. - Marni Wesner; Terry Defreitas; Heather Bredy; Louisa Pothier; Ziling Qin; Ashley B McKillop; Douglas P Gross (PLoS ONE)
Objective This pilot study aimed to inform future research evaluating the effectiveness of Platelet Rich Plasma (PRP) injection for tendinopathy. Design Randomized control trial (RCT) and synchronous observational cohort studies. For the RCT, consecutive consenting patients treated at an academic sports medicine clinic were randomly assigned to either a PRP or placebo control group. Setting The Glen Sather Sport Medicine Clinic, Edmonton, Canada. Patients The RCT included 9 participants with rotator cuff tendinopathy. The cohort study included 178 participants with a variety of tendinopathies. Interventions Patients receiving PRP were injected with 4 ml of platelets into the supraspinatus and/or infraspinatus, while patients in the placebo group were injected with 4 ml of saline. All participants undertook a 3-month standardized, home-based, daily exercise program. Main outcome measures Participants in the RCT were re-evaluated 3, and 6 months post-injection. Change scores before and after injection on pain, disability and MRI-documented pathology outcomes were compared. In the cohort study, pain and disability were measured at 1, 2 and 3 months post-injection. Results For the RCT, 7 participants received PRP and 2 received placebo injections. Patients receiving PRP reported clinically important improvements in pain (>1.5/10 on VAS), disability (>15 point DASH change), and tendon pathology while those receiving placebo injections did not. In the observational cohort, statistically and clinically significant improvements in pain and disability were observed. Conclusion This pilot study provides information for planning future studies of PRP effectiveness. Preliminary results indicate intratendinous, ultrasound-guided PRP injection may lead to improvements in pain, function, and MRI-documented tendon pathology. Trial registration Controlled-Trials.com ISRCTN68341698.